Promoting health and physical capacity during productive work: the Goldilocks Principle - Andreas Holtermann; SvendErik Mathiassen; Leon Straker (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: In spite of preventive efforts, organizations and employees face several challenges related to working life and occupational health, such as a substantial prevalence of musculoskeletal disorders, social inequality in health and physical capacity, multi-morbidity, an obesity epidemic and an aging workforce. We argue that a new approach to occupational ergonomics and health is required, going beyond prevention of harm caused by work. We propose the "Goldilocks Principle" for how productive work can be designed to promote health and physical capacity. METHODS: Physical (in)activity profoundly influences health and physical capacity, with effects depending on the extent and temporal structure of the (in)activity. Like the porridge, chair and bed that needed to be "just right" for Goldilocks in the The Three Bears fairytale, physical activity during productive work needs to be "just right" for promoting rather than deteriorating health and capacity. In many jobs, physical activity is, however, either too much/high/frequent or too little/low/infrequent to give positive biomechanical and cardiometabolic stimuli. RESULTS: This paper presents the rationale, concept, development, application and prospects of the Goldilocks Principle for how productive work can be designed to promote health and physical capacity. CONCLUSIONS: We envision a great potential to promote health and physical capacity by designing productive work according to the Goldilocks Principle, thus leading to benefits with respect to the current challenges related to working life and occupational health for society, organizations and employees.